Malignant mesothelioma of peritoneum: about an observation - Estefan, Alberto; Gómez Fossati, Carlos; de Stefani, Eduardo (Cirugía del Uruguay, 1973)
For the first time in national case material, or so we believe, there is a case of diffuse, papilar, malign mesothelioma in the omentum majus infiltrated in colon, stomach, splenic and pancreatic capsule and liver. It was slighlty round. For this reason the author reviews pathology, diagnosis and treatment of this rare disease.